Examining the contact filter paper method in the low suction range - Leong, Eng Choon (2021)
The filter paper method for measuring suction is standardized in ASTM D5298-16, Standard Test Method for the Measurement of Soil Potential (Suction) Using Filter Paper. The contact filter paper is usually calibrated using a pressure plate apparatus from 10 to 1,500 kPa. The filter paper calibration curve is commonly plotted on a log-log or semilog graph with water content as the abscissa and suction as the ordinate. To evaluate the accuracy of the filter paper calibration curve in the low suction range (<10 kPa), the Whatman No. 42 filter paper is assessed using the capillary-rise method for suction range from 0.1 to 1.6 kPa and using the Tempe cell for suction range from 3 to 7 kPa. The test results from the capillary-rise method and Tempe cell tests show different trends. The difference in trends is attributed to the limitation of the axis-translation technique used in the Tempe cell test, which is not applicable at a high degree of saturation. The capillary-rise method shows that the Whatman No. 42 filter paper has a maximum water content of about 135 % and minimum measurable suction of about 1 kPa. The water content of the filter paper at 1 kPa suction can be used to supplement the other method for suctions greater than 10 kPa to give the calibration curve of the Whatman No. 42 filter paper.